Role of the Community Reinvestment Act in Mortgage Supply and the U.S. Housing Boom - Saadi, Vahid (Review of Financial Studies, 2020)
Abstract This paper studies the role of the Community Reinvestment Act (CRA) in the U.S. housing boom-bust cycle. I find that enhanced CRA enforcement in 1998 increased the growth rate of mortgage lending by CRA-regulated banks to CRA-eligible census tracts. I show that during the boom period house price growth was higher in the eligible census tracts because of the shift in mortgage supply of regulated banks. Consequently, these census tracts experienced a worse housing bust. I find that CRA-induced mortgages were awarded to borrowers with lower FICO scores and were more frequently delinquent.